A Qualitative Exploration of Teachers’ Experiences of Bullying by Learners- A Job Demands Resources Perspective - Masoka, Petunia Ntokozo (University of the Witwatersrand, Johannesburg, 2024)
Abstract Teacher-Targeted Bullying and Harassment by learners (TTBH) has been identified as an issue in South African schools. TTBH negatively affects the psychological and physiological well- being of teachers, their willingness to stay in the profession, and the overall quality of education in South African schools. This study utilised the theoretical model of the Job Demands Resources Model and a qualitative methodology to understand teachers' experiences and perceptions of this type of workplace bullying. It further utilised the Frustration- Aggression Hypothesis, Social Learning Theory, and Bronfenbrenner’s Ecological Theory to understand possible causes of TTBH. The data was collected using semi-structured interviews and was analysed using Thematic Content Analysis. Twelve participants (9 females and 3 males) were interviewed from a number of schools within the Central Gauteng region. Eight participants identified as black (n=8), and four participants identified as coloured (n=4). All the participants in this study were from schools in Quintile four. The main themes that emerged were demands faced by teachers which include changes in curriculum, lack of resources as well as the impact of social and environmental factors that affect the process of teaching and learning. Furthermore, the effects of TTBH on teachers and schools, coping mechanisms, and how TTBH in South African schools can be mitigated were other themes that emerged from the interviews. Based on the findings of this study a number of interventions were suggested that include policies and procedures that protect teachers, counselling services for teachers and learners and greater parental involvement and support.
A research report Submitted in fulfillment of the requirements for a Master of Arts Organisational Psychology, In the Faculty of Humanities , School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; Teacher-Targeted Bullying and Harassment (TTBH); Resources; Demands; Workplace bullying; Teachers; Coping; Intervention; SDG-4: Quality education